Morphological Characterization of Saprophyte Fungi on Cocoa Fruit Peel Litter - Tanzil, Ahmad Ilham; Efendi, Soleudin; Dewi, Nilasari; Kurnianto, Agung Sih (Talenta Publisher, 2023)
Cocoa is an important commodity crop in Indonesia. However, current obstacles related to the problem of cocoa shell litter which is slow to decompose are an obstacle in plantation management. Therefore it is necessary to conduct research related to the exploration and identification of saprophytic fungi in cocoa pod litter. Samples of cocoa pod litter were taken at PTPN XII, while the isolation and identification processes were carried out at the Mycology Laboratory, Department of Plant Pests and Diseases, Faculty of Agriculture, Universitas Brawijaya. From the results of macroscopic and microscopic identification, nine isolates of saprophytic fungi were obtained consisting of seven genera, namely Candida sp., Penicillium sp., Fusidium sp., Rhizopus sp., Chepalosporium sp., Trichoderma sp.1, Trichoderma sp.2, Aspergillus sp., and Trichoderma sp. 3.